2020
DOI: 10.21037/atm.2020.02.126
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy after lung transplantation

Abstract: Lung transplantation is an established therapeutic option for selected patients with advanced lung diseases. As early outcomes after lung transplantation have improved, chronic medical illnesses have emerged as significant obstacles to long-term survival. Among them is post-transplant malignancy, currently representing the 2 nd most common cause of death 5-10 years after transplantation. Chronic immunosuppressive therapy and resulting impairment of anti-tumor immune surveillance is thought to have a central ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 107 publications
(173 reference statements)
1
23
0
6
Order By: Relevance
“…Lung‐transplant recipients are at increased risk of malignancy due to long‐term immunosuppression 21 . Moreover, our and previous data showed that lung cancers are among the most common malignancy after LTx 22‐24 . Malignant pleural effusions are associated with an increased mortality, 25,26 an association that was confirmed by our survival data of patients with late‐onset effusions.…”
Section: Discussionsupporting
confidence: 80%
“…Lung‐transplant recipients are at increased risk of malignancy due to long‐term immunosuppression 21 . Moreover, our and previous data showed that lung cancers are among the most common malignancy after LTx 22‐24 . Malignant pleural effusions are associated with an increased mortality, 25,26 an association that was confirmed by our survival data of patients with late‐onset effusions.…”
Section: Discussionsupporting
confidence: 80%
“…PTLD is diagnosed when EBV levels start to rise in association with an abnormal white cell count, and is more common in lung transplant recipients than most other SOT recipients. It occurs in 2-9% of lung transplant recipients [101,102]. Early cases (within 1 year of transplantation) typically involve the lungs and occur in recipients who have not previously been exposed to the virus, whereas cases presenting more than 1 year post-transplantation are more likely to involve the gastrointestinal (GI) tract [101].…”
Section: Malignancymentioning
confidence: 99%
“…Early-onset PTLD is more likely to respond to a reduction in immunosuppression than late-onset as the pathogenesis of the latter is less well understood, but this in turn increases the risk of rejection and graft failure [104]. As a result, prognosis with late-onset PTLD is worse [102,105]. If reduction in treatment is not the solution, the next option would be rituximab, which induces cell death of B-cells via CD20 which is on the surface of these cells.…”
Section: Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…С учетом неуклонно возрастающего количества трансплантаций солидных органов во всем мире (только за 2020 год в мире выполнено 113 363 трансплантации солидных органов) и постепенного увеличения продолжительности жизни реципиентов донорских органов актуальность изучения злокачественных новообразований будет только возрастать. Вопросы развития онкозаболеваний у этой категории достаточно подробно освещены в иностранной литературе, тогда как отечественных источников мы не нашли [1][2][3][4][5][6][7][8][9][10][11][12][13]30].…”
Section: Introductionunclassified